Scientific Approaches to Definition of Essence of Ecological-economical Security of the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In article scientific approaches to definition of essence of safety in general and ecological-economical security in particular are considered. On the basis of generalization of the received results the main signs of each of concepts are defined. It is revealed that concerning subjects of managing, safety is often considered as a condition of the enterprise; result of effective activity of management of the enterprise; condition of its sustainable development. Using of a synthesis method allowed to improve definition of essence of ecological-economical security of the enterprise as conditions of its security from negative impacts, thanks to internal stability, preservations of self-identity and integrity, flexibility and adaptability that provides ability to stable development, realization of strategic objectives, achievement of desirable results without damage to an environment, preservation of natural resources and assimilatory potential of environment. The article founds specific features of ecological-economical security.
Keywords: safety, economic security, ecological safety, ecological-economical security of the enterprise